Hubungan Antara Self efficacy Akademik dengan Perilaku Mencontek (Cheating) Selama Masa Daring Siswa SMA X - Ella Dwi Nurjayanti; Nurlaela Widyarini; Anggraeni Swastika Sari (Indonesian Journal Publisher, 2023)
Online learning is a distance education system with a teaching method where there are teaching activities carried out separately from learning activities (Mustofa et all, 2019). The online learning process only focuses on cognitive development processes (Gusmaniarti, 2020). This research aims to determine the relationship between self-efficacy and cheating behavior in SMA X students during the online period. The research respondents were high school students in class X (X, XI and XII) with a population of 750 with a sample of 238 students. The sampling technique uses purposive sampling. This type of research is quantitative correlational. The scale used is the cheating behavior scale adapted from Ginanjar Mukti Priaswandy (2015) with a validity of 0.311 to 0.762 and a reliability of 0.861, while the self-efficacy scale is adapted from Anggraeni Swastika Sari (2013) with a validity value of 0.25 and a reliability of 0.710. Based on the results of the correlation analysis, the correlation coefficient was -0.776 (negative) with a significance value smaller than probability (0.000 ≤ 0.05). This means that if self-efficacy is low then cheating behavior is also low among SMA X students during the online period.